Iterated integral transforms of Caratheodory functions and their applications to analytic and univalent functions - Babalola, K. O.; Opoola, T. O. (Tamkang Journal of Mathematics, 2006)
In this paper we develop and study some integral transforms of Caratheodory functions. We apply the transforms to study certain other classes of analytic and univalent functions both to obtain new results and provide new proofs of some known ones.